Ancient Roots Of The Art Of Baxshi And Favorite Epics Of The Uzbek People (Zien Journal of Social Sciences and Humanities, 2022)
The article deals with the Uzbek folk epic and its spiritual foundations, its place in our national values, historical significance, the relevance of the art of baxshi, spiritual and national achievements in the field of baxshi and epic poetry, favorite epics of the Uzbek people and devotion of the Uzbek people to the motherland in the epics, to keep the soil of the homeland sacred, to miss the homeland, to preserve it like the apple of an eye, to hate enemies, issues such as physical vigor, the idea of resolving everything on the basis of peace, on the basis of advice, are explained in a comprehensive way.